The Effect of Access to Toll Road Construction on Interest in Buying Housing (Housing Case Study at Bukit Cimanggu Bogor) - Kuraesin, Ecin (INOVATOR, 2023)
This study aims to analyze the effect of access to the construction of the BORR Toll Road Access 3 on the interest in buying housing in Bukit Cimanggu, Bogor. The source of this research data is primary data that comes from the sample, namely respondents who are buyers and will buy houses in housing areas in the Bogor area around the toll road construction. Data was collected by distributing questionnaires to 100 respondents. The data analysis method used is the technique of multiple linear regression analysis using the SPSS 23.0 program. The results of the study show that transactional, referential, preferential, and exploratory consumer interest in consumer decisions to buy houses near the construction of the BORR toll road as faster and easier transportation access shows a high or strong relationship. And the type of consumer interest also has a positive and significant impact or influence on consumer decisions to buy houses in the BCC housing.